Paisagens e imagens em trânsito: os bolivianos no Exílio paulistano - Rodrigues, Pedro Roberto (2020)
This research aims to analyze from the anthropology ofthe image of Hans Belting and Dietmar Kamper the transformation of the body into an image causing the loss of its dimension (Pross) and consequently of the visibility, in what Prof. Dr. Norval Baitello Junior calls it an era of iconophagy, in which images are devoured by others due to the acceleration of the time of their contemplation. Since the pre-lncan period5 the Bolivian immigrant suffered losses, a great deal of gold, trees, birds, animals and people were taken to Europe; regions were taken over by Brazil and Chile; dictatorial governments handed over mining to the United States and England; and recently the growth of informal work again forced them to be a nomad, having to cross bridges and migrate. In order to survive in the City of São Paulo, this immigrant is subjected to the precarious conditions of work in sewing workshops under conditions similar to slave labor. Sometimes driven by the tertiary media, but above all, by a network of contacts of family and friends in Brazil. The image of this immigrant date back to Colombo's arrival in America and to a 'colonization of images" in the imaginary and in everyday life. The imposition of a language, Christianization, the idea of superiority of the colonizer and drug trafficking today mark this body and make them exiled in São Paulo. However, from machine body to invisible body, they transcend and resist with feast